Kosakata Pinjaman dalam Pemakaian Bahasa Bali pada Mingguan Bali Orti di Koran Bali Post Edisi Januari-Juni Tahun 2018 - Ni Kadek Heni Sulyantari Dewi (Dharma Sastra: Jurnal Penelitian Bahasa dan Sastra Daerah, 2021)
Use of loan vocabulary from other language especially, English in Balinese language become important to be studied at this time. Some of the English loan vocabulary actually equivqlences in Balinese language. The use of loan vocabulary certainly has an impact in the attitude of Balinese speaker. In this research the researcher reviewing: 1) kinds of English the loan vocabulary in Balinese language; 2) The factor causing loan vocabulary; 3) the attitude of Balinese speaker towards the loan vocabulary. Relating to the kinds the loan vocabulary are classified into two: 1) based on the levelof frequency and extent of usage they are devided into two kinds, that is speech loans for example: now, discontinue, net control, and example language loan: outbond, modern; 2) based of factor causing loan devided into two are loands need example: now, spiritual, discontinue, instrument. Furthermore, the factor that cause the occurrence of English loan vocabulary are caused by three factors, such as: 1) the borrower does not find an equvqlent word in the Balinese language; 2) expressive power of lost word; 3) difference in certain social values in the language involved. Then relating to the attitude of the language of Balinese speakers declarethem selves to be positive toward Balinese language, but the people also received the entry of loan vocabulary from English in the use of Balinese language.